Effect of deboning time on the growth of Salmonella, E. coli, aerobic, and lactic acid bacteria during beef sausage processing and storage. (May 2018) - Sukumaran, Anuraj T.; Holtcamp, Alexander J.; Englishbey, April K.; Campbell, Yan L.; Kim, Taejo; Schilling, Mark W.; Dinh, Thu T.N.
Abstract: The objective of the current study was to determine the effects of deboning time, three steps of sausage processing (grinding, salting, and batter formulation), and storage time (of raw materials and cooked sausage) on the growth (log CFU/g) of aerobic bacteria, lactic acid bacteria, and inoculated Salmonella and E. coli . Beef deboning time did not influence bacterial counts ( P  ≥ 0.138). However, salting of raw ground beef resulted in a 0.4-log reduction in both aerobic plate count (APC) and Salmonella ( P  ≤ 0.001). Lactic acid bacteria were increased from non-detectable concentration (0.54 log) on d 0 to 3.8 log on d 120 of vacuum storage ( P  ≤ 0.019). Salmonella counts were increased ( P  < 0.001) over storage time (3.2 to 3.3 log CFU/g from d 0 to 10). Results indicated that salting and batter formulation had a greater impact on bacterial counts than rigor state of raw beef.